Language Testing for Minority Students in Portuguese Schools: Teacher’s Decision Making Based in Common European Framework - Figueiredo, Sandra (2018)
Recent research on cognitive and academic performance assessment of immigrant students evidences inconsistencies in teachers’ practice regarding performance assessment of L2 students. We aim to verify whether students classified by schools as having different proficiency levels in accordance to the Common European Framework of Reference for Languages (CEFR, 2001) perform differently in tests on vocabulary and verbal reasoning. The study included 23 learners of Portuguese as L2 aged 9-18, divided into three groups according to their proficiency level (A1, A2, B1). Assessment tools included four tasks - verbal analogies, semantic associations, picture naming and morphological extraction. Our expectations are that A1 students perform more poorly in all tasks than A2 students and that these perform more poorly than students classified as having a B1 level in Portuguese language. Results show that, on the one hand, there are performance differences among proficiency groups and, on the other hand, there is inconsistency in the expected order of performance differences in the tasks (from the beginner to the most advanced level). Results suggest inconsistencies in teachers’ practice regarding testing of the performance of minority groups with implications in the academic success of the identified students.